Dosimetric effect of variable rectum and sigmoid colon filling during carbon ion radiotherapy to sacral chordoma. (October 2021) - Ricotti, R.; Pella, A.; Mirandola, A.; Fiore, M.R.; Chalaszczyk, A.; Paganelli, C.; Antonioli, L.; Vai, A.; Tagaste, B.; Belotti, G.; Rossi, M.; Ciocca, M.; et al.
Highlights: Carbon ion radiotherapy to sacral chordoma is sensitive to bowel density variations. Density overwrite on planning CT models realistic intestinal filling conditions. Dosimetric perturbation caused by density variations is evaluated prior treatment. Abstract: Purpose: Carbon ion radiotherapy (CIRT) is sensitive to anatomical density variations. We examined the dosimetric effect of variable intestinal filling condition during CIRT to ten sacral chordoma patients. Methods: For each patient, eight virtual computed tomography scans (vCTs) were generated by varying the density distribution within the rectum and the sigmoid in the planning computed tomography (pCT) with a density override approach mimicking a heterogeneous combination of gas and feces. Totally full and empty intestinal preparations were modelled. In addition, five different intestinal filling conditions were modelled by a mixed density pattern derived from two combined and weighted Gaussian distributions simulating gas and feces respectively. Finally, a patient-specific mixing proportion was estimated by evaluating the daily amount of gas detected in the cone beam computed tomography (CBCT). Dose distribution was recalculated on each vCT and dose volume histograms (DVHs) were examined. Results: No target coverage degradation was observed at different vCTs. Rectum and sigma dose degradation ranged respectively between: [−6.7; 21.6]GyE and [−0.7; 15.4]GyE for D50% ; [−377.4; 1197.9] and [−95.2; 1027.5] for AUC; [−1.2; 10.7]GyE and [−2.6; 21.5]GyE for D1% . Conclusions: Variation of intestinal density can greatly influence the penetration depth of charged particle and might compromise dose distribution. In particular cases, with large clinical target volume in very close proximity to rectum and sigmoid colon, it is appropriate to evaluate the amount of gas present in the daily CBCT images even if it is totally included in the reference planning structures.